Examination of maximum mouth opening and ear canal movement using the earable RCC - OMORI, Fumitaka; MIYAZAKI, Masaru; KAJII, Takashi; UNOKI, Ayumi; KUROKI, Keiji; YAMANO, Takafumi (jibi to rinsho, 2020)
The earable RCC is a device that measures the change in the shape of the ear canal based on the change in the relative distance between an optical distance sensor and the eardrum. We examined the relationship between the maximum mouth opening of healthy individuals and ear canal movement using this device. It was useful for the measurement of ear canal movement with maximum opening movement and could also be used for the objective assessment of ear canal movements in patients with temporomandibular disorders.